Stability and risk in cocoa-laurel-plantain agroforestry system - Ludewigs, T. (1997)
9 fig. 6 tab. Bib. p. 42-43. Sum. (En, Es). Avances de investigación en: Agroforestería en las Américas (IICA) (no.17-18) p. 17-22. (Ene-Jun 1998).